Evaluation value of serum SP⁃D，CCL25 and pulmonary vascular resistance index on the degree of lung injury and prognosis in traumatic wet lung - LIU Yajian，HU Zhuosi，CAO Xuexia，ZHAO Lianlian，LIU Junjuan，QIN Yanjun (Zhongguo linchuang yanjiu)
Objective To explore the relationship between serum surfactant protein D（SP⁃D），C⁃C motif chemokine ligand 25（CCL25）and pulmonary vascular resistance index（PVRI）with the degree of lung injury and prognosis in severe chest trauma patients complicated with traumatic wet lung（TWL），and to analyze their clinical evaluation values. Methods A total of 160 patients with severe chest trauma and TWL admitted to Hebei Medical University Third Hospital from January 2020 to February 2024 were enrolled. Based on the severity of lung injury，they were divided into mild⁃to⁃moderate group（n=68）and severe group（n=92）. Three indexes（PVRI，serum SP⁃D，CCL25) and lung injury score（LIS）were compared between different lung injury degree groups，and the correlation of these three indexes with LIS scores and their impact on the prognosis of patients with TWL were analyzed. The predictive values of these three indicators on the degree of lung injury and prognosis of patients with TWL were evaluated. Results The mild ⁃ to ⁃moderate group had significantly lower PVRI，serum SP⁃D，CCL25，and LIS scores compared to the severe group（P<0.01）. Correlation analysis revealed positive associations between PVRI，SP⁃D，CCL25，and LIS（r=0.707，0.776， 0.779，P<0.05）. The combined assessment of PVRI，SP⁃D，and CCL25 for severe lung injury yielded an area under the receiver operating characteristic（ROC）curve（AUC）of 0.920（95%CI：0.866-0.957），with a sensitivity of 85.87% and a specificity of 85.29% . Among the 160 patients，114 survived and 46 died within 30 days. The survival group exhibited lower APACHE Ⅱ scores，PVRI，SP⁃D，and CCL25 levels than the non⁃survival group（P<0.05）. Logistic regression identified APACHE Ⅱ score，PVRI，SP⁃D，and CCL25 as independent risk factors for mortality（P<0.05）. The combined assessment of PVRI，SP⁃D，and CCL25 for prognosis had an AUC of 0.939（95%CI：0.890-0.970），with a sensitivity of 91.30% and specificity of 84.21%. Conclusion PVRI，serum SP⁃D，and CCL25 are significantly associated with the severity of lung injury in severe chest trauma complicated with TWL and hold high predictive values for both lung injury severity and prognosis.